Influence of the Quality of Implementation of Islamic Corporate Governance and Complexity on the Frequency of Fraud in Sharia Banking in Indonesia - Suharto, Suharto; DS, Priyarsono; Andati, Trias (Budapest International Research and Critics University, 2021)
The purpose of this study is to explore the quality of Islamic Corporate Governance in sharia banking in Indonesia and analyze the effect of the quality of Islamic Corporate Governance implementation and bank complexity on the frequency of fraud in sharia banking in Indonesia from 2011 through 2020. This study uses a descriptive method with a quantitative approach. The population in this study were all Indonesian sharia commercial banks based on banking statistics issued by the Financial Services Authority (OJK) in December 2020, which were 14 sharia commercial banking, then selected by the purposive sampling method using sharia commercial banking criteria that reported a complete self-assessment report during 2011 – 2020, which is as many as 10 sharia commercial banking. The type of data used is secondary data whose data collection is carried out by online data search methods through website searches. The data analysis method used panel data regression. The results of the study showed that the quality of Islamic Corporate Governance implementation at sharia commercial banking during 2011 - 2020 on average had a